Characterization of avian influenza H5N3 reassortants isolated from migratory waterfowl and domestic ducks in China from 2015 to 2018. Issue 6 (26th August 2019) - Li, Xuyong; Cui, Pengfei; Zeng, Xianying; Jiang, Yongping; Li, Yubao; Yang, Jiaxin; Pan, Yudi; Gao, Xinxin; Zhao, Conghui; Wang, Jinhui; Wang, Kai; Deng, Guohua; et al.
Abstract: Wild and domestic aquatic birds are the natural reservoirs of avian influenza viruses (AIVs). All subtypes of AIVs, including 16 hemagglutinin (HA) and nine neuraminidase (NA), have been isolated from the waterfowls. The H5 viruses in wild birds display distinct biological differences from their highly pathogenic H5 counterparts. Here, we isolated seven H5N3 AIVs including three from wild birds and four from domestic ducks in China from 2015 to 2018. The isolation sites of all the seven viruses were located in the region of the East Asian‐Australasian Migratory Flyway. Phylogenetic analysis indicated that the surface genes of these viruses originated from the wild bird H5 HA subtype and the N3 Eurasian lineage. The internal genes of the seven H5N3 isolates are derived from the five gene donors isolated from the wild birds or ducks in Eastern‐Asia region. They were also divided into five genotypes according to their surface genes and internal gene combinations. Interestingly, two of the seven H5N3 viruses contributed their partial internal gene segments (PB1, M and NS) to the newly emerged H7N4 reassortants, which have caused first human H7N4 infection in China in 2018. Moreover, we found that the H5N3 virus used in this study react with the anti‐serum of the H5 subtype vaccine isolate (Re‐11 and Re‐12) and reacted well with the Re‐12 anti‐serum. Our findings suggest that worldwide intensive surveillance and the H5 vaccination (Re‐11 and Re‐12) in domestic ducks are needed to monitor the emergence of novel H5N3 reassortants in wild birds and domestic ducks and to prevent H5N3 viruses transmission from the apparently healthy wild birds and domestic ducks to chickens.